Utility of the Brain Injury Screening Index in Identifying Female Prisoners With a Traumatic Brain Injury and Associated Cognitive Impairment. (October 2019) - O'Sullivan, Michelle; Fitzsimons, Steven; Ramos, Sara da Silva; Oddy, Michael; Glorney, Emily; Sterr, Annette
There is a high prevalence of traumatic brain injury (TBI) in prisoners, but screening tools for identifying TBI in female prisoners are not readily available. Using a cross-sectional design, the psychometric properties of the Brain Injury Screening Index (BISI) were investigated in a closed United Kingdom female prison. Purposive sampling comprised 56 females. Assessment included clinical interview, the BISI, self-report measures of mood, and a battery of measures of cognitive functioning. Seven of the 10 clinical indicators on the BISI met test–retest reliability criteria. Two of the three BISI summary variables demonstrated correlations with questionnaires in the hypothesized directions; however, only two BISI variables were associated with cognitive functioning. Findings support further investigation into the validity and reliability of the BISI with a larger sample.